2018
DOI: 10.1200/jgo.18.12500
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cancer Early Detection Training Program for Primary Healthcare Providers

Abstract: Background and context: Over 250,000 new pediatric cancer cases are diagnosed yearly worldwide. Health care providers (mainly nurses) at health centers (HC) level are the children´s first opportunity for correctly recognizing and responding to early signs and symptoms of childhood cancers by appropriately referring them to district hospitals but studies show that 83% of nurses did not receive training on pediatric cancers. Insufficient knowledge about the warning signs and symptoms of pediatric cancer usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…All 12 studies were published between 2004 and 2018. Ten studies (83%) were conducted in a single LMIC, 14,16,17,[22][23][24][25][26][27][28] while two (17%) were conducted across multiple LMICs. 15,18 All 12 studies used a pre-post design to evaluate the effectiveness of their interventions, comparing postintervention data to baseline data collected retrospectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…All 12 studies were published between 2004 and 2018. Ten studies (83%) were conducted in a single LMIC, 14,16,17,[22][23][24][25][26][27][28] while two (17%) were conducted across multiple LMICs. 15,18 All 12 studies used a pre-post design to evaluate the effectiveness of their interventions, comparing postintervention data to baseline data collected retrospectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies (42%) 14,16,18,22,23 focused on retinoblastoma only, while the remaining seven (58%) 15,17,[24][25][26][27][28] focused on all childhood cancer types. Six studies (50%) 14,22,[24][25][26]28 evaluated interventions that targeted health care professionals, while four studies(33%) 15,17,18,23 reported on training of health care professionals and public awareness campaigns. Two studies (17%) 16,27 focused on public awareness campaigns only.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations